Cell macroencapsulation devices in contemporary research: A systematic review - Murillo D.L. Bernardi; Natascha Rus; Robin W.M. Vernooij; Marianne C. Verhaar; Maarten B. Rookmaaker (Regenerative Therapy)
Cell macroencapsulation devices (CMDs) represent a promising therapeutic approach by combining controlled, off-the-shelf technology with living tissue functionality. Despite their potential, the current knowledge about CMD development and implementation remains fragmented across different applications. We conducted a systematic review to synthesize the available evidence on implantable CMDs and establish a comprehensive framework for their development. Our analysis cataloged studies based on device materials and design, cell types, implantation strategies, and evaluation methods. The review revealed that CMD development has largely progressed in application-specific silos, with varying approaches to device characterization, cell selection (from xenogeneic to autologous), and assessment methods. Key evaluation parameters included cell survival and functionality, host tissue response (inflammation, vascularization, and fibrosis), and therapeutic efficacy. While successful implementations exist across multiple applications, the lack of standardized development and evaluation protocols emerges as a significant barrier to cross-application advancement. These findings highlight the need for unified assessment frameworks to accelerate CMD development across therapeutic applications.